2021
DOI: 10.3389/fnmol.2021.661993
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Maternal Separation Modifies Proteostasis Marker Expression in the Adult Hippocampus

Abstract: Exposure to early-life stress (ELS) can persistently modify neuronal circuits and functions, and contribute to the expression of misfolded and aggregated proteins that are hallmarks of several neurodegenerative diseases. The healthy brain is able to clear dysfunctional proteins through the ubiquitin-proteasome system (UPS) and the autophagy-lysosomal pathway (ALP). Accumulating evidence indicates that impairment of these pathways contributes to enhanced protein aggregation and neurodegeneration. While stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 131 publications
2
4
0
Order By: Relevance
“…With an unbiased WGCNA analysis, we identified an ELS-associated gene module in P200 microglia specifically related to protein ubiquitination and degradation of ubiquitinylated proteins, consistent with reported alterations in the ubiquitin-proteasome system in the hippocampus and cortex of adult rats exposed to maternal separation (65). Ubiquitin is crucial for protein degradation processes and is also involved in pathways such as inflammation (66).…”
Section: Discussionsupporting
confidence: 80%
“…With an unbiased WGCNA analysis, we identified an ELS-associated gene module in P200 microglia specifically related to protein ubiquitination and degradation of ubiquitinylated proteins, consistent with reported alterations in the ubiquitin-proteasome system in the hippocampus and cortex of adult rats exposed to maternal separation (65). Ubiquitin is crucial for protein degradation processes and is also involved in pathways such as inflammation (66).…”
Section: Discussionsupporting
confidence: 80%
“…With an unbiased weighted gene co-expression network analysis (WGCNA) analysis, we identified an ELS-associated gene module in P200 microglia specifically related to protein ubiquitination and degradation of ubiquitinated proteins, consistent with reported alterations in the ubiquitin-proteasome system in the hippocampus and cortex of adult rats exposed to maternal separation [72]. Ubiquitin is crucial for protein degradation processes and is also involved in inflammatory pathways [73].…”
Section: Discussionsupporting
confidence: 75%
“…MS with its structural, developmental, neuroendocrine, and neurochemical changes in different areas of the brain such as the amygdala nucleus, prefrontal cortex, and hippocampus causes mood and behavioral disorders; These changes in the nervous system provide the basis for the occurrence of several neurodegenerative diseases in the adulthood including depression, Alzheimer's disease, etc. (Sierra‐Fonseca et al, 2021; Tanaka et al, 2021). Studies on ASD patients indicated defects in brain development as well as structural and endocrinal disturbances.…”
Section: Discussionmentioning
confidence: 99%